29 Influence of dietary manganese source on the corpus luteum proteome in pigs. (30th November 2020) - Studer, Jamie M; Kiefer, Zoe; Keating, Aileen F; Baumgard, Lance H; Olsen, Kristin M; Rambo, Zachary; Wilson, Mark E; Rapp, Christof; Ross, Jason W
Abstract: Functional corpora lutea (CL) are required for pregnancy establishment and gestational maintenance in swine. Manganese (Mn) could be critical in regulating CL function since it is a cofactor for the enzyme Mn superoxide dismutase (Mn-SOD) as well as enzymes involved in progesterone (P4 ) synthesis. We hypothesized a more bioavailable dietary Mn source would increase CL Mn content thereby influencing luteal function during the mid-luteal phase of the estrous cycle. Post-pubertal gilts (n = 32) were assigned to one of four gestation diets. The control diet (CON) met or exceeded NRC requirements and was formulated to contain 20 ppm added Mn in the form of Mn sulfate. Three additional diets included 20 (TRT1), 40 (TRT2) or 60 (TRT3) ppm Mn from a Mn-amino acid complex (Availa-Mn; Zinpro Corporation) in place of Mn sulfate. Dietary treatment began at estrus synchronization onset and continued through D12 of the ensuing estrous cycle when gilts were euthanized. Mn content increased (P ≤ 0.06) 19, 21 and 24% in CLs of gilts fed TRT1, TRT2, and TRT3, respectively, and luteal P4 concentration decreased (P ≤ 0.03) 25, 26, and 32% in gilts fed TRT1, TRT2, and TRT3, respectively, compared to CON. Total CL protein was extracted and liquid chromatography with tandem mass spectrometry (LC-MS/MS) was performed to assess global protein abundance. Compared to CON, 29, 105, and 118 proteins were differentially abundant (P < 0.01) in TRT1, TRT2, and TRT3, respectively. KEGG pathway analysis revealed proteins involved in P4 signaling (membrane-associated P4 receptor component 2) and cholesterol synthesis and transport (mevalonate kinase, diphosphomevalonate decarboxylase, low density lipoprotein receptor) were downregulated in response to Availa-Mn. Collectively, these data support the posit that dietary Mn source affects Mn accumulation and P4 concentration in CL tissue and influences protein abundance which may affect CL function.